2009
DOI: 10.1038/ijo.2009.159
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrient-specific effect of FTO rs9939609 in response to a 10-week randomized hypo-energetic diet among obese Europeans

Abstract: Background: The A risk allele of rs9939609 of the fat mass-and obesity-associated gene (FTO) increases body fat mass. Objective: To examine whether FTO rs9939609 affects obese individuals' response to a high-fat, low-carbohydrate (CHO) (HF) or low-fat, high-CHO (LF), hypo-energetic diet and whether the effect of the FTO variant depends on dietary fat and CHO content. Design: In a 10-week, European, multi-centre dietary intervention study 771 obese women and men were randomized to either LF (20-25% of energy (%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 36 publications
(53 reference statements)
2
54
1
2
Order By: Relevance
“…In this meta-analysis, each selected study was considered to be a single study unit, and mean weight loss by the FTO genotype groups in the overall study sample, regardless of intervention differences, was taken into account. For studies that reported weight loss for intervention groups separately (15,18,27), we combined the results of different groups with the use of the combining method recommended by the Cochrane Handbook for Systematic Reviews of Interventions (30). We used the same method to combine results of the FTO TA and AA genotype groups for studies that provided results of additive genetic models (16-21, 24, 31).…”
Section: Data Synthesis and Statistical Analysismentioning
confidence: 99%
“…In this meta-analysis, each selected study was considered to be a single study unit, and mean weight loss by the FTO genotype groups in the overall study sample, regardless of intervention differences, was taken into account. For studies that reported weight loss for intervention groups separately (15,18,27), we combined the results of different groups with the use of the combining method recommended by the Cochrane Handbook for Systematic Reviews of Interventions (30). We used the same method to combine results of the FTO TA and AA genotype groups for studies that provided results of additive genetic models (16-21, 24, 31).…”
Section: Data Synthesis and Statistical Analysismentioning
confidence: 99%
“…There is a renewed popularity of low carbohydrate high fat diets, as well as the scientific study of them (Foster et al 2003;Volek et al 2003;Yancy et al 2004). Indeed, it now appears that genes contribute to whether one will drop out of a low calorie diet depending on whether it is low fat or high fat (Grau et al 2009). Despite these changes in society, high quality food has always featured animal fats because of their taste and during the past 40 years there has been no deviation from that practice (Escoffier 1921;Bocuse 1988;Carluccio and Contaldo 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Four randomised controlled trials were identified that presented evidence on diets differing in the proportion of carbohydrate to fat or protein in relation to blood glucose response two hours after an oral glucose tolerance test (Swinburn et al, 2001;Lasker et al, 2008;Due et al, 2008a). No further trials were identified in the update search (Cardio-metabolic review, diabetes chapter p185) (Racette et al, 1995;Golay et al, 1996;Golay et al, 2000;Swinburn et al, 2001;Helge, 2002;Colette et al, 2003;Landry et al, 2003;Lovejoy et al, 2003;Wolever & Mehling, 2003;Clifton et al, 2004;Segal-Isaacson et al, 2004;Dansinger et al, 2005;Lofgren et al, 2005;Raatz et al, 2005;Petersen et al, 2006;Howard et al, 2006b;Ebbeling et al, 2007;Gardner et al, 2007;Maki et al, 2007b;Phillips et al, 2008;Due et al, 2008a;Frisch et al, 2009;Grau et al, 2009;Kirk et al, 2009;Morgan et al, 2009;Sacks et al, 2009). Five trials were subsequently identified in the update search (Goree et al, 2011;Haufe et al, 2011;Shikany et al, 2011;Tierney et al, 2011;Brooking et al, 2012 Nearly all trials employ energy restricted weight loss diets that vary both carbohydrate (between 5% and 65% energy) and fat (between 18% and 40% energy) between groups.…”
Section: Cohort Studiesmentioning
confidence: 99%
“…Thirteen randomised controlled trials were identified that presented evidence on diets differing in the proportion of carbohydrate to fat on measures of insulin resistance/sensitivity (Helge, 2002;Wolever & Mehling, 2002;Foster et al, 2003;Lofgren et al, 2005;Raatz et al, 2005;Johnston et al, 2006;Maki et al, 2007b;Tinker et al, 2008;Due et al, 2008a;Grau et al, 2009;Kirk et al, 2009;Sacks et al, 2009;de Luis et al, 2009a). Five trials were subsequently identified in the update search Goree et al, 2011;Haufe et al, 2011;Shikany et al, 2011;Tierney et al, 2011) 5.105.…”
Section: Insulin Resistance/sensitivitymentioning
confidence: 99%
See 1 more Smart Citation